Keeping Emilia-Romagna strong: an integrated industrial policy approach - Annaflavia Bianchi; Patrizio Bianchi (Wirtschaftsdienst, 2019)
Almost five decades after the creation of institutional governments at the regional level in Italy and the transfer of policy responsibilities to the regional administrations, this paper focuses on the more recent policy experience of Emilia-Romagna, in particular, its 2015 'patto per il lavoro' (Deal for Labour). It follows an integrated approach to industrial policy at the regional level and attempts to extract the most from available resources, based on a constant exchange with other regions, the Italien state, the European Commission and other external institutions. The main axis on which all the other elements turn are, in addition to the leverage of research and innovation, education and training.
Keywords: J10; L50; O52; 330